2016
DOI: 10.18203/2320-1770.ijrcog20162121
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based case control study of female breast cancer risk factors in a Sub-Saharan African country

Abstract: INTRODUCTIONBreast cancer is the most common cancer diagnosed in women worldwide with over 1.3 million new cases per year. There is a wide variation in the geographical burden of the disease with the highest incidences seen in the developed regions of the world and the lowest incidences observed in the least developed regions. ABSTRACTBackground: Breast cancer is the most common cancer diagnosed in women worldwide with over 1.3 million new cases per year. There is a wide variation in the geographical burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Family history is an important risk factor for breast cancer and is significantly greater in women with a family history of the disease. 24,28,54 Similarly, in this study, family history has significantly associated with the risk of breast cancer. However, this finding is in contrast with the results of a previous similar study conducted in Vietnam, which indicated that there was no significant association between family history and breast cancer.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Family history is an important risk factor for breast cancer and is significantly greater in women with a family history of the disease. 24,28,54 Similarly, in this study, family history has significantly associated with the risk of breast cancer. However, this finding is in contrast with the results of a previous similar study conducted in Vietnam, which indicated that there was no significant association between family history and breast cancer.…”
Section: Discussionsupporting
confidence: 65%
“…The sample size was calculated using Epi-Info version 7.2 based on the following assumptions: 95% confidence interval, 80% power, and 1:2 ratio of cases to controls, 24.3% proportion of family history of breast cancer in Senegal Dakar with an odds ratio of 2.12 28 and a 10% non-response rate. This yields a maximum sample size of 116 cases and 232 controls.…”
Section: Methodsmentioning
confidence: 99%
“…50 Reproductive factors including early menarche and menopausal status have been acclaimed breast cancer risk factors; however, no association was found between these risk factors and breast cancer in Senegalese women. 51 Some breast cancers have been attributed to postmenopausal body mass index (Figure 5) globally. Possibly, many more risk factors are unexplored; hence there is an urgent need to exhaustively investigate breast cancer-associated risk factors in SSA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…52 Early age at diagnosis and a positive breast cancer history may be suggestive of familial predispositions, which have not been thoroughly investigated in the SSA population. 51 Women with a familial breast cancer history with one or two first-degree premenopausal breast cancer relatives are at a 3.3-fold and 3.6fold greater risk of developing breast cancer, respectively, compared to women without a family history. 53 Approximately 13-19% of diagnosed breast cancer patients had an affected first-degree relative.…”
Section: Risk Factorsmentioning
confidence: 99%
“…5 Among the identified risk determinants of breast cancer include age, family history, medical history, weight, physical activity, alcohol consumption, cigarette smoking, breastfeeding, parity, menopausal status, stress, vegetable intake, fruit intake, and oral contraceptive use. [6][7][8][9][10][11][12] No studies have been performed to analyze the risk factors for breast cancer in Ethiopia. The present study may add information on evidence of risk factors for breast cancer in Ethiopia and supporting evidence to reduce the burden of the disease.…”
Section: Introductionmentioning
confidence: 99%